Exploration of the burnout syndrome occurrence among mental health nurses in Cyprus - Papathanassoglou, Elizabeth; Karanikola, Maria (My University, 2013)
Nurses' work-related stress might be associated with psychiatric symptoms, leading to altered professional attitudes. The aim of this study was to explore the levels of burnout and associations with anxiety and depressive symptoms among Greek-Cypriot psychiatric–mental health nurses (PMHNs). A descriptive correlational design with cross-sectional comparisons was applied. A sample of 226 PMHNs was used. Participants reported low levels of burnout. However, 10% of them manifested clinically significant anxiety and depressive symptoms. Emotional exhaustion and depersonalization were associated with depressive (r = 0.562, p b 0.0001, and r = 0.616, p b 0.0001, respectively) and anxiety (r = 0.394, p b 0.0001, and r = 0.448, p b 0.0001, respectively) symptoms. Further research investigating the biological aetiopathology of these psychological alterations is warranted.
Keywords: Anxiety disorders; Burnout; Depressive disorder; Diagnosis; Epidemiology; Health service